Contribution a l'etude de la conformation du betail local Rwanda de type Ankole - Compere, R. (1964)
Studies body conformation of Ankole cattle reared at the Zootechnic Centre at Nyamiyaga, Rwanda. Sixteen measurements were effected on a routine basis on 400 heads of bulls and cows during their growing period. Data on the rhythm of development of examined cattle, correlations between live weight and principal dimensions of body measurements included. Based on the findings, improvement of actual body conformation of Ankole was emphasized.